If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 = 3(x + -6) Reorder the terms: 3 = 3(-6 + x) 3 = (-6 * 3 + x * 3) 3 = (-18 + 3x) Solving 3 = -18 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 3 + -3x = -18 + 3x + -3x Combine like terms: 3x + -3x = 0 3 + -3x = -18 + 0 3 + -3x = -18 Add '-3' to each side of the equation. 3 + -3 + -3x = -18 + -3 Combine like terms: 3 + -3 = 0 0 + -3x = -18 + -3 -3x = -18 + -3 Combine like terms: -18 + -3 = -21 -3x = -21 Divide each side by '-3'. x = 7 Simplifying x = 7
| .6666(x+5)=-10+4 | | -29+7x=x-8/4 | | 4m=110 | | -2v=-12 | | 4m= | | x^2-100x+1600=0 | | 1=-5n+4n | | -5r=15 | | x/10+2.5=7.5 | | X=5y+41 | | 1/6(16-4a)-3/4(12+20a) | | y-3/5=2(1/4) | | 9d-2d-6d+4-4d=0 | | 6(3n-1)=(7n+4)+7 | | 0.6(x-5)=-10+4 | | (16+2x)(28+2x)=748 | | 4x-4-2x=4 | | p-46=-11 | | 0.92+x(0.2)=y | | 8=2w+7/6+7w+6/2 | | (-5u+7w-z)/(u+w-z) | | b/7-13=12 | | Y-5x=13 | | x^2+10x=200 | | 4(4x+3)+6=16x+18 | | 120(n-3)=600 | | 4(y+3)+y=2(y+4)-4 | | 5.4x+3.4=14.2 | | 2x^2+5x^4-12x^3=0 | | 2x-3/9+x+1/2=x-4 | | -24+6x=8(3x+6) | | -b+1.8=5.3 |